2016
DOI: 10.14442/jgfm.17.4_289
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Respiratory Rehabilitation for the Frail Elderly: a Pilot Study

Abstract: Objective: To analyze the effects of respiratory rehabilitation on the activities of daily living (ADL) and quality of life (QOL) in community-dwelling frail elderly.Design: Pilot intervention study after a one-year period of observation.Setting: Day care facility in a rehabilitation hospital.Subjects: Thirty community-dwelling frail elderly using rehabilitation services Intervention: After a one-year observation period of usual rehabilitation, 30 participants were given 12 rehabilitation sessions that include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…Rosińczuk 2 ) and colleagues reported that while QOL of patients with COPD is not affected by gender, decline in QOL level is associated with age and pulmonary function. In the present study, the participants did not include those with COPD; however, in our previous studies, we reported that pulmonary function decreased in community-dwelling frail older persons even without COPD and also showed an association between pulmonary function and ADL/QOL 13 , 14 ) .…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Rosińczuk 2 ) and colleagues reported that while QOL of patients with COPD is not affected by gender, decline in QOL level is associated with age and pulmonary function. In the present study, the participants did not include those with COPD; however, in our previous studies, we reported that pulmonary function decreased in community-dwelling frail older persons even without COPD and also showed an association between pulmonary function and ADL/QOL 13 , 14 ) .…”
Section: Discussionmentioning
confidence: 74%
“…In the present study, the participants did not include those with COPD; however, in our previous studies, we reported that pulmonary function decreased in community-dwelling frail older persons even without COPD and also showed an association between pulmonary function and ADL/QOL 13,14) .…”
Section: Discussionmentioning
confidence: 74%
“…The inclusion criteria included the following: history of stroke diagnosed by clinicians and needing rehabilitation, more than 65 years of age, 6 months since acute disease onset, and period since stroke onset of >6 months, and being in a physical condition that can be described as “frail” as defined by the Fried Frailty Criteria (Cardiovascular Health Study: CHS index) 13 . Participants who could not use an auto spirometer or with moderate or severe cardiac disease (New York Heart Association 14 Classification of III or IV) 7,15 were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…For the intervention group, each 20‐min rehabilitation session was held once a day and was made up of 10 mins of pulmonary training in addition to 10 min of standard rehabilitation 7,15 . The pulmonary training intervention comprised the following: pulmonary muscle training, stretching exercise, and home exercise 7,15,16 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation